Effectiveness and safety of once-weekly semaglutide: findings from the SEMACOL-REAL retrospective multicentric observational study in Colombia - Buenaventura-Collazos, Daisy C.; García-Ramos, Andrés F.; Balcázar-Valencia, Carlos M.; Aguilar-Londoño, Carolina; Coronel-Restrepo, Nicolás; Monsalve-Arango, Claudia Y.; Cuesta-Castro, Diana P.; Ramírez-Rincón, Alex (Frontiers in Endocrinology, 2024)
Introduction: Diabetes stands as one of the leading causes of death worldwide. Glucagon-like peptide-1 receptor agonists rank among the most effective medications for lowering blood glucose and body weight, as well as reducing cardiovascular risk in individuals with diabetes. Observational studies complement experimental evidence in new settings, different populations, and real-world healthcare practices. Methods: Multicentric observational study of adults with type 2 diabetes treated with once-weekly subcutaneous semaglutide in four health centers in Colombia. The protocol for the present study was not pre-registered. Results: Data from 186 patients was included. Most patients were women (57%) with a mean age of 62.8 ±12.1 years. One year of once-weekly semaglutide usage was associated with a mean reduction in HbA1C of - 1.47 % (95%CI -1.76, -1.17), weight loss of -4.23 kg (95%CI -5.34, -3.12), and albumin/creatinine ratio of -18.6 mg/g (CI95% -60.2, -5.9). Around half the treated patients achieved a level of HbA1c ≤7% by the end of follow-up. Adverse events were rare and consistent with clinical trial safety profiles. Conclusion: In Colombia, administering semaglutide subcutaneously once a week over a one-year period led to an average weight loss of 4.2 kg and a decrease of 1.4% in HbA1c.